Assessing the Modulatory Effects of Biochar on Soil Health Status in Response to Pesticide Application - Giovanna B. Melas; Oriol Ortiz; Amira M. Roshdy; Mohamed Y. Hendawi; Dimitrios Triantakonstantis; Sameh Shaddad (Earth)
Considering the global competition to increase food productivity due to the increasing population growth, the use of chemical pesticides has become the quick solution, but by increasing awareness about the serious dangers of wasteful chemicals in various areas of life, it has become necessary to move immediately, albeit gradually, towards safe biological treatments. From this point of view, the use of biochar is one of the trends in reducing soil pollution with chemical pesticides. Therefore, the main objectives of this work are (i) to assess if the application of three pesticides based on imidacloprid, methyl thiophanate, and glyphosate has detectable adverse consequences on soil organisms’ activity and (ii) to evaluate if the addition of biochar modifies the effects of these chemicals. An agricultural soil was amended with different doses of biochar. The treated soil received realistic amounts of currently used pesticides. Samples were stored at 21 °C and 50% WHC (water holding capacity) for a period of 28 days under dark conditions. Oxygen consumption was measured for 12 consecutive hours after the addition of 2.5 g glucose kg−1 as a stimulant for soil organisms. Biomass C was estimated from the difference between the amount of C in 0.5 M K2SO4 extracts of CHCl3 fumigated soil and the extractable C in non-fumigated samples. Specific respiration was computed as the amount of O2 consumed per unit of Biomass Carbon. The results of this work proved that the tested biochar could modulate the effects produced by the agrochemicals on soil biomass.